Protocol-Based Reliable Control for Power Systems with Communication Constraints - Yong Chen; Meng Li; Song Li; Yunhui Wang; Min Xie; Yongkun Yang (Complexity)
This study focuses on the protocol-based control for single-area power systems subject to actuator failures and deception attacks. Specifically, actuator failures, network attacks, unreliability, and bandwidth restrictions that emerge in power systems are taken into consideration at the same time. To cut down on the number of broadcast packets, a novel memory-adaptive event-triggered protocol is developed, where the trigger threshold parameter is adaptively changed in accordance with numerous historical sampled signals. Then, in virtue of the proposed algorithm, sufficient stabilization conditions are acquired to ensure the asymptotically stable of power systems with H∞ performance. Finally, the efficiency of the proposed control strategy is demonstrated by using a simulation example.